2000
DOI: 10.1002/pen.11251
|View full text |Cite
|
Sign up to set email alerts
|

Production of injection molding tooling with conformal cooling channels using the three dimensional printing process

Abstract: A Solid Freeform Fabrication Process called Three Dimensional Printing is applied to the fabrication of injection molding tooling with cooling channels which are conformal to the molding cavity. The tool is created by spreading layers of stainless steel powder and selectviely joining the powder in the layers by ink‐jet printing of a binder material. Unbound powder is removed from without and within the green part thus defined. The green part is sintered and infiltrated with a copper alloy to produce a fully de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(131 citation statements)
references
References 3 publications
3
122
0
6
Order By: Relevance
“…13). Early research [280] [359][129] [267] showed that conformal cooling in injection molding tooling improves process efficiency and quality. Industrial injection molding case studies have confirmed these benefits with reports of reduced lead time, more uniform temperature distributions, reduced cycle times, improved quality, reduced reject rates, reduced corrosion, longer maintenance intervals, and overall cost savings [98][108] [112].…”
Section: Internal Freeform Geometry For Functionality and Performancementioning
confidence: 99%
“…13). Early research [280] [359][129] [267] showed that conformal cooling in injection molding tooling improves process efficiency and quality. Industrial injection molding case studies have confirmed these benefits with reports of reduced lead time, more uniform temperature distributions, reduced cycle times, improved quality, reduced reject rates, reduced corrosion, longer maintenance intervals, and overall cost savings [98][108] [112].…”
Section: Internal Freeform Geometry For Functionality and Performancementioning
confidence: 99%
“…They showed that the conformal cooling channels technique led to significant improvements and a general reduction of the cycle time while increasing heat transfer (Ring et al, 2002). A comparison between conformal channels and drilled cooling channels has also been conducted by Sachs et al Their analysis shows that the conformal channel mould reaches operational temperature faster than the conventional one, attaining a more uniform temperature distribution with efficient heat transfer capacity (Sachs et al, 2000). While the use of conformal cooling channels on the one hand greatly enhances the injection molding process, on the other hand it is much more complicated fabricate them on respect of the straight ones.…”
Section: Tools With Three-dimensional Conformal Channelsmentioning
confidence: 99%
“…Enhanced heat extraction, increased production rate and reduced cost can thus be achieved. Conformal cooling channels can be made by depositing sacrificial material, which is later removed as with MITs 3DP process [37], or can be made while fabricating the part as with Optomec's LENS process [16]. Another example of part complexity is the casting for a fuel cross over made for Rocketdyne by Soligen's 3DP process [36].…”
Section: The Promise Of Lmmentioning
confidence: 99%